Emotional Intelligence and Success - Neaga, Susanu (New Trends in Psychology, 2023)
Emotional intelligence has existed and evolved with humanity. The human brain reflects this undeniable fact. Advanced scanning techniques have recently confirmed that many thought processes pass through the emotional centres of the brain as they move into the physiological area designed to convert external information into individual action and response. In other words, emotion is as old as time. The authors who developed the EQ papers organised them into five domains: the intrapersonal domain; the interpersonal domain; the adaptability domain; the stress management domain; and the general state domain. This domain of EQ encompasses what we generally call “our self”. It determines how you perceive your feelings about how satisfied you are with yourself and what you are doing in life. Success in this area means that you are able to express your feelings, live and work independently, feel empowered and confident in expressing your ideas and opinions.